Sindrom Vena Kava Superior pada Pasien dengan Timoma Stadium III - Jersivindo Ranazeri; Alexander Kam; Roza Kurniati; Fauzar Fauzar (Fakultas Kedokteran, Universitas Andalas, 2021)
A 50 year old man presented with superior vena cava syndrome. Superior vena cava syndrome is one of the emergency oncology cases. After the diagnostic procedure, the patient was diagnosed with stage III thymoma. With chemotherapy regimens of cisplatin 50 mg/m2, doxorubicin 50 mg/m2 and cyclophosphamide 500 mg/m2, the patient experienced clinical improvement.